Off-Label Prescribing in Pediatric Inpatients With Pneumonia in a Children's Hospitaal - Hesty Utami Ramadaniati; Heni Safarini; Aishah A Regine (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
Off-label is a term used in which a drug prescribed outside the official information of the marketing authorization. Off-label prescribing may occur as the result of several factors including lack of clinical trials data involving pediatrics and suitable formulations for medicines commonly prescribed to this fragile population. Objective: This study aimed to estimate the nature and prevalence of off-label prescribing in pediatric inpatients with pneumonia. Material and Methods: a retrospective study was conducted in a study hospital using medical records from pediatric inpatients with pneumonia during the period of January-December 2015. Patient and prescribing data were collected, and drugs were classified as on-label or off-label based on the Indonesia National Drug Information (IONI) and British National Formulary for Children (BNFC). Thereafter, off-label drugs were categorized with a hierarchical system of age, indication, route of administration and dosage. Results: There were 1141 drugs with 77 different types of drug were administered to 207 patient during the study period. The data uncovered that 405 (35,5%) of the drug prescriptions were used off-label based on IONI, and 319 (28%) of the drug were used off-label based on BNFC. Based on IONI and BNFC, most off-label drugs were from anti infection drugs. Conclusion: The prevalence of off-label use in pediatric inpatients with pneumonia is not high. The off-label prescribing may not be necessarily be considered irrational, yet this fact reveals that the use of drugs does not comply with the drug label. Clinical trials for pediatric drugs are essential to provide complete product information for pediatric use.